New Cloud System Metrics to Assess Bulk Ice Cloud Schemes in a GCM - Claudia J. Stubenrauch; Marine Bonazzola; Sofia E. Protopapadaki; Ionela Musat (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Bulk microphysical properties of ice clouds, such as fall speed and ice crystal size distribution, strongly impact the life time and the radiative effects of these clouds. Three coherent bulk ice schemes, with fall speed and effective ice crystal diameter depending on both ice water content and temperature, have been constructed from published parameterizations. We present a novel upper tropospheric cloud system concept to study the impact of these schemes on the LMDZ climate simulations. For this evaluation, cloud data from hyperspectral infrared sounders Atmospheric InfraRed Sounder and IR Atmospheric Sounding Interferometer are used, because they include cirrus with visible optical depths as low as 0.2. The analogous satellite observation simulator, developed for this purpose, is also presented. The cloud system concept, applied to the data and to the simulator outputs, allows a process‐oriented evaluation. In general, the new bulk ice schemes lead to a better agreement with the cloud data, in particular concerning the cloud system property distributions and the relation between cloud system properties and proxies mimicking the life stage and the convective depth. Sensitivity studies have demonstrated that both the introduction of the new schemes as well as the necessary adjustment of the relative width of the upper tropospheric subgrid water distribution lead to these improvements. Our studies also suggest to revise the formulation of the latter.